Analisis Pengaruh Rekrutmen dan Pelatihan Kerja Dalam Meningkatkan Kompetensi Karyawan di PT. Bersih Harum Sehat Produsen Homecare Brand Nucclean di Indonesia - Rosmawati Agustini (Jurnal Akuntansi, Manajemen dan Ekonomi Digital, 2022)
capital and assets that are important in the company to support the running of a company. The company organization will not run and grow well, without the support of reliable and competent human resources. In today's competition in the economic field, every company strives and is required to obtain the right and competent human resources in order to encourage the success of their business so that they are able to compete with other companies. Management of human resources should receive more attention by the company so that the organization is able to achieve the vision, mission and goals of the company effectively. PT.Bersih Harum Sehat is an organization that produces Homecare Brand Nuclean in Indonesia. In this study aims to analyze how the influence of recruitment and job training in improving the competence of employees at PT. Bersih Harum Sehat as a manufacturer of Homecare Brand Nucclean in Indonesia. The results of the study indicate that the recruitment variable (X1) tcount > ttable and the job training variable (X2) tcount > ttable. Based on the test criteria if tcount > ttable, then H0 is rejected and Ha is accepted, which means that recruitment (X1), and job training (X2) affect employee competence (Y), where the variable Recruitment (X1), and Job Training (X2) provides positive and significant influence on employee competence (Y). Keywords: Recruitment, Job Training and Competence